Importancia del conocimiento de las propiedades fisicoquímicas del herbicida Glifosato - Santamaria Cusme, Kevin Alejandro (2024)
The present document addresses the importance of understanding the physicochemical properties of the herbicide Glyphosate to comprehend its environmental behavior. This compound, widely used in agriculture, exhibits characteristics that make it persistent in soil and with low volatility, raising concerns about its impact on the environment. Although Glyphosate is considered to be relatively non-toxic, its extensive use has raised concerns about weed resistance and potential contamination of food and water sources. Detailed research into its properties in agricultural and natural environments is crucial to evaluate its effects on biodiversity and surrounding ecosystems. A comprehensive understanding of its physicochemical properties is necessary to develop safer and more sustainable agricultural policies. This involves examining Glyphosate's effects on soil health, biodiversity, and aquatic ecosystems, as well as promoting agricultural practices that minimize its negative impact. In summary, detailed knowledge of Glyphosate is essential to address the environmental challenges associated with its use in agriculture.